PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN D’BESTO PADA CABANG MERUYUNG DI KOTA DEPOK JAWA BARAT - Nur Alam, Iqra; Mustakim, Masran (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of product quality and price on consumer satisfaction at D'Besto Meruyung Branch, Depok City, West Java. The method used is a quantitative method. The sampling technique used is Probability Sampling with Random Sampling type. The number of samples used in this research was 100 respondents. Data analysis techniques use instrument tests, namely validity and reliability tests, classic assumption tests, namely normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple linear regression test, correlation coefficient test, coefficient of determination and hypothesis test. tests, namely the t test and F test. The results of this research are that product quality has a significant effect on consumer satisfaction with the regression equation Y = 21.324 + 0.487X1. Hypothesis testing obtained a value of tcount> ttable (6.681>1.660). Price has a significant effect on customer satisfaction with the regression equation Y = 15.191+0.625X2. Hypothesis testing obtained a value of tcount> ttable (8.623>1.660). Product quality and price simultaneously have a significant effect on customer satisfaction with the regression equation Y= 12.894+0.207X1+0.481X2. Hypothesis testing obtained a value of fcount > ftable (42.150 > 3.090). Thus it can be concluded that product quality and price have a positive and significant effect on customer satisfaction.